Mapping the global, regional, and national burden of diarrheal diseases attributable to unsafe water - Chen, Ling; Jiao, Jinghua; Liu, Shunming; Liu, Lei; Liu, Pengliang (Frontiers in Public Health, 2023)
Background Diarrheal diseases are major contributors to deaths. Data on global and country-specific levels and trends of diarrheal diseases resulting from unsafe water are essential for policymakers to allocate resources. Aims This study aimed to describe the global, regional, and national spatiotemporal burden of diarrheal diseases resulting from unsafe water exposure. Methods According to the Global Burden of Disease (GBD) 2019 dataset, deaths, disability-adjusted life years (DALYs) of diarrheal diseases, and their age-standardized rates (ASRs) were analyzed by age and sex in 204 countries and territories. Moreover, the average annual percentage change (AAPC) was estimated by a log-linear regression model to reflect the time trend. The association between ASR of diarrheal diseases due to unsafe water and socio-demographic index (SDI) levels was also analyzed. Results From 1990 to 2019, the number of deaths and DALYs of diarrheal diseases resulting from unsafe water decreased by 50 and 59%, respectively. Moreover, the ASR of deaths and DALYs also decreased during the study period, with AAPCs of −3.69 (95% CI [95% confidence interval]: −3.91 to −3.47) and − 3.66 (95% CI: −3.8 to −3.52), respectively. High diarrheal diseases resulting from unsafe water occurred mainly in low SDI regions and Africa. Males exhibited greater diarrheal deaths attributable to unsafe water than females, which was contrary to the condition in terms of DALYs. The age-specific burden of diarrheal deaths attributable to unsafe water is concentrated in children younger than 5 years. The AAPCs of the ASR of both deaths and DALYs showed a strong negative correlation with the SDI levels. Conclusion The current study indicated that the global burden of unsafe water exposure-related diarrheal diseases decreased from 1990 to 2019 and varied significantly according to age, sex, and geographical location. Effective health promotion and health communication strategies and policies should be adopted to prevent and control diarrheal diseases resulting from unsafe water exposure.